2017
DOI: 10.1093/pcp/pcx027
|View full text |Cite
|
Sign up to set email alerts
|

Ozone-Sensitive Arabidopsis Mutants with Deficiencies in Photorespiratory Enzymes

Abstract: An ozone-sensitive mutant was isolated from T-DNA-tagged lines of Arabidopsis thaliana. The T-DNA was inserted at a locus on chromosome 3, where two genes encoding glycolate oxidases, GOX1 and GOX2, peroxisomal enzymes involved in photorespiration, reside contiguously. The amounts of the mutant's foliar transcripts for these genes were reduced, and glycolate oxidase activity was approximately 60% of that of the wild-type plants. No difference in growth and appearance was observed between the mutant and the wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…The main function of the photorespiratory pathway is the efficient removal of critical intermediates, especially 2-PG, which severely inhibits carbon fixation and allocation [6,10]. Furthermore, it has been suggested that photorespiration plays a role in the abiotic stress response of plants [25][26][27]. Therefore, we hypothesized that an increased photorespiratory flux might facilitate plant abiotic stress tolerance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The main function of the photorespiratory pathway is the efficient removal of critical intermediates, especially 2-PG, which severely inhibits carbon fixation and allocation [6,10]. Furthermore, it has been suggested that photorespiration plays a role in the abiotic stress response of plants [25][26][27]. Therefore, we hypothesized that an increased photorespiratory flux might facilitate plant abiotic stress tolerance.…”
Section: Discussionmentioning
confidence: 97%
“…Apart from the central role of photorespiration supporting photosynthetic CO 2 fixation, it has been suggested that it plays also a role in the stress response of plants. For example, malfunctioning of photorespiration leads to an enhanced susceptibility of the plants against pathogen attack [22,23], and lowered tolerance towards abiotic stresses [24][25][26][27]. This is mainly because photorespiration serves as alternative energy sink under unfavorable environmental conditions regenerating ADP and NADP and, thus, decreases acceptor limitation of the light process and related ROS formation [26,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Free and total SA concentrations were determined by high‐performance liquid chromatography–fluorescence as outlined in Han et al (). Glycolate content was measured by liquid chromatography–tandem mass spectrometry (Agilent), using 5% acetic acid extracts from leaves as described in Saji et al ().…”
Section: Methodsmentioning
confidence: 99%
“…The level of sensitivity to O 3 within Arabidopsis is subject to natural genetic variation (Brosché et al, ). In addition, a number of induced mutants with enhanced O 3 sensitivity have been identified (Overmyer et al, ; Overmyer et al, ; Rao, Lee, & Davis, ; Saji et al, ; Saji et al, ; Vainonen & Kangasjärvi, ). These are defective in various physiological pathways that likely are interconnected functionally with each other (Overmyer et al, ).…”
Section: Introductionmentioning
confidence: 99%